Rate of recolonization of the major arthropoda taxa inhabiting saraca roots in a tropical mountain stream - Shaharudin Abdul Razak (Universiti Kebangsaan Malaysia, 2004)
A study of the major Arthropoda taxa of invertebrates recolonizing Saraca roots occurring on various substrates and under various water velocities was carried out in the upper reaches of the Gombak River. The sites for the recolonization experiments were selected in the fast and slow flowing sections of rocks and boulders, sand and gravel and mud and silt biotopes. The Hydropsychidae and the Nemouridae were the pioneer recolonizers of Saraea roots in the fast flowing sections of the stream whereas the Ptilodactylidae and the Caenidae were the pioneer recolonizers in the slow flowing sections of the stream.